Somatic Embryo Enhancing of Phalaenopsis amabilis (L.) Blume Orchid with 6-Benzyl Amino Purine (BAP) - Karend, Azzah Hanun Abas; Setiari, Nintya; Nurchayati, Yulita; Rashid, Fatimah Azzahra Ahmad (Universitas Negeri Surabaya, 2025)
Phalaenopsis amabilis (L.) Blume is an orchid with high economic value because of its beautiful white flowers, yellow labellum, and long stems. Its existence in nature is threatened with extinction, so efforts are needed to cultivate and preserve P. amabilis, one of which is through somatic embryos, which generally require Plant Growth Regulators (PGRs) in the form of 6-Benzyl Amino Purine (BAP). 6-Benzyl Amino Purine (BAP) is used because it is one of the cytokinin hormones proven to induce somatic embryos. This study aims to examine and determine the use of the right BAP concentration to propagate P. amabilis through somatic embryo induction. The explants used were P. amabilis protocorms; because protocorms produced a greater number of somatic embryos than leaf explants, the development of the explants was observed every week for 2 months. This study used a single factor Completely Randomized Design (CRD) in the form of BAP concentrations of 0, 1, 2, 3, and 4 ppm with 20 replications. The results showed that the most optimal treatment for the propagation of P. amabilis somatic embryos was on media with an average number of somatic embryos at a concentration of BAP 3 ppm (65.00) embryo/explain.